2009
DOI: 10.1093/qjmed/hcn140
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and peripheral artery disease

Abstract: Peripheral arterial disease (PAD) is an important healthcare problem and is an indicator of widespread atherosclerosis in other vascular territories, such as the cerebral and coronary circulations. PAD is associated with considerable morbidity and mortality. Most population-based studies investigating PAD prevalence and risk factors for its development and progression have been based on predominantly White ethnic groups. Much less is known about the characteristics of this disease in other ethnic groups. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 163 publications
(202 reference statements)
1
40
1
1
Order By: Relevance
“…SA studies suggest that the ethnic differences found in PAD prevalence are related to the heterogeneity of risk factors found in SAs where traditional risk factors alone do not explain the higher cardiovascular burden in this ethnic group 3. While smoking is a strong risk factor for PAD, smoking rates are generally less in SAs (particularly in females) than WEs; however, adjustment for smoking rates or pack years does not explain the ethnic discrepancy in PAD prevalence 3 18.…”
Section: Discussionmentioning
confidence: 96%
“…SA studies suggest that the ethnic differences found in PAD prevalence are related to the heterogeneity of risk factors found in SAs where traditional risk factors alone do not explain the higher cardiovascular burden in this ethnic group 3. While smoking is a strong risk factor for PAD, smoking rates are generally less in SAs (particularly in females) than WEs; however, adjustment for smoking rates or pack years does not explain the ethnic discrepancy in PAD prevalence 3 18.…”
Section: Discussionmentioning
confidence: 96%
“…Peripheral arterial disease causes intractable ischemia, impaired mobility, compromised wound healing, ulceration, and amputations (1,2). EPC transplantation has been suggested as an angiogenic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The age-adjusted prevalence of peripheral arterial disease is approximately 12%, and affects men and women equally. The typical clinical manifestation is claudication, nevertheless 5% ofpatients undergo an amputation within 5 years (1,2). …”
mentioning
confidence: 99%
“…Bennett et al 66 reported that elevated or high SBP and DBP are major independent risk factors for CHD and stroke. The Prospective Studies Collaboration 67 noted that in those 40 to 69 years of age, the risk of death from stroke or heart disease increases more than 2-fold for every SBP increment of 20 mm/Hg or DBP increment of 10 mm/Hg, beginning with an SBP of 115 mm/Hg and a DBP of 75 mm/Hg.…”
Section: Hypertensionmentioning
confidence: 99%